The Impact of Czechoslovakia’s Party System on the Disintegration of the Common State - Marcin Czyżniewski (Polish Political Science Yearbook, 2025)
Against the background of modern federal states, the party system in Czechoslovakia was unique. Its characteristic feature was the existence of parallel party systems created by parties representing individual nations. Thus, we are referring to separate Czech and Slovak systems. This paper analyzes the impact of the Czechoslovak party system’s peculiarities on the fate of the common state, including the decision to abolish it. The author hypothesizes that the peculiarities of the Czechoslovak party system were instrumental in the breakup of the Czech-Slovak federation. It created the conditions to make the demands of the new organisation of the federation an essential issue in the political competition. It did not allow the development of conditions or mechanisms to control the process. The article can support and create arguments in the discussion of the ideal party system in federal and multi-ethnic states.